The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.jhep.2010.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human liver sinusoidal endothelial cell by human platelets induces hepatocyte proliferation

Abstract: Platelets promote LSEC proliferation and induce IL-6 and VEGF production. Direct contact between the platelets and LSECs and S1P, that are contained in platelets, were involved in the excretion of IL-6 from LSECs. IL-6 from LSECs induced proliferation of parenchymal hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 37 publications
1
88
1
Order By: Relevance
“…Platelets promote hepatocyte proliferation and have an anti-fibrotic effect in vitro (Matsuo et al 2008;Kawasaki et al 2010;Ikeda et al 2011), and thrombocytosis promotes liver regeneration and reduces liver fibrosis in vivo (Murata et al 2007;Murata et al 2008b;Myronovych et al 2008;Watanabe et al 2009). We hypothesized that platelet increment therapy would improve liver function in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelets promote hepatocyte proliferation and have an anti-fibrotic effect in vitro (Matsuo et al 2008;Kawasaki et al 2010;Ikeda et al 2011), and thrombocytosis promotes liver regeneration and reduces liver fibrosis in vivo (Murata et al 2007;Murata et al 2008b;Myronovych et al 2008;Watanabe et al 2009). We hypothesized that platelet increment therapy would improve liver function in humans.…”
Section: Discussionmentioning
confidence: 99%
“…When the liver is injured, platelets accumulate in the injured liver and actively translocate into Disse spaces Nakamura 1992, 1993;Nakamura et al 1998;Murata et al 2007;Myronovych et al 2008). The direct contact between platelets and hepatocytes or LSECs is necessary for hepatocyte proliferation (Matsuo et al 2008;Kawasaki et al 2010), and the direct contact between platelets and HSCs is essential for an anti-fibrotic effect (Ikeda et al 2011). Taken together, the previous and current data suggest that transfused platelets delivered to the portal vein accumulate in the damaged liver due to CLD; directly contact hepatocytes, LSECs, and HSCs; and finally improve liver function and reduce liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*p < 0.05 versus S1P-group. (Reproduced from Kawasaki et al, 2010, J Hepatol with permission.) The direct contact between platelets and LSECs triggers excretion of S1P from platelets, which subsequently causes excretion of IL-6 from LSECs.…”
Section: The Role Of Kupffer Cells On Liver Regenerationmentioning
confidence: 99%
“…Some studies suggest that local release of growth factors or angiogenic molecules stored within platelet alpha and dense granules are responsible for platelet-mediated liver regeneration [4,[13][14][15][16]. Even though it has been reported that platelet-derived growth factors stimulate hepatocyte proliferation in vitro [13,14,17], it has not yet been established whether platelet-derived growth factors also drive platelet-mediated liver regeneration in vivo [12]. Animal studies and a single study in humans have demonstrated accumulation of platelets within the liver remnant rapidly following a partial liver resection [5,16,18].…”
Section: Introductionmentioning
confidence: 99%